What do patients want to know about contraception and which method would they prefer? - Oppelt, Patricia; Baier, Friederike; Fahlbusch, Christine; Heusinger, Katharina; Hildebrandt, Thomas; Breuel, Christiane; Dittrich, Ralf (Archives of Gynecology and Obstetrics, 2017)
PURPOSE: The aim of this study was to determine the extent to which women's choice of contraceptive method depends on the advice received from their gynecologist and whether more intensive counseling might lead to more frequent use of long-acting reversible contraception (LARC). METHODS: A total of 1089 physicians and 18,521 women responded to 32 or 37 questions, respectively, using an online questionnaire. The women were asked about their current use of contraceptive methods, the extent of their satisfaction with them, their satisfaction with the counseling they had received, and whether they wanted to have more information about contraception. The physicians were similarly asked which contraceptive methods were being used, how satisfied with them they were, how they would assess their patients' satisfaction with them, and whether the women wanted to have more information. RESULT: The results showed that 61% of the women were using oral contraceptives, and a total of only 9% were using behavior-independent long-term contraceptive methods. However, 60% of the women stated that long-term contraception would be an option for them if they had more information about it. Gynecologists underestimated this figure, at only 18%. Whereas 66% of the gynecologists believed that their patients never forgot to take the pill, nearly, half of the women stated that they had forgotten it at least once during the previous 3 months. CONCLUSION: The small number of women who use long-term contraception is in clear contrast to the fact that many women want to have a very safe but also behavior-independent method.
EVALuna2:36175